Beyond motives to adopt: Implementation configurations and implementation extensiveness of a voluntary sustainability standard. (1st April 2020) - Smits, Armand; Drabe, Viktoria; Herstatt, Cornelius
Abstract: Most studies that explain implementations of voluntary sustainability standards (VSS) have directly connected motives to adopt to implementation extensiveness as the endpoint, without sufficiently considering what happens in between. This has led to inconclusive and limited findings. This study addresses this lacuna by investigating the combined effects of the commonly discussed internal and external motives to adopt and several implementation characteristics on implementation extensiveness. Given the causal complexity of VSS implementations, the present study adopts a configurational lens and applies fuzzy-set Qualitative Comparative Analysis (fsQCA). It is based on both quantitative and qualitative data on 43 firms implementing the Cradle to Cradle standard, a VSS related to the Circular Economy school of thought. Results are augmented with in-depth cases of firms that follow dominant implementation paths. This study identifies seven implementation configurations and illustrates how the impact of motives to adopt on implementation extensiveness hinges on the presence or absence of implementation characteristics, such as the nature of implementation experiences. It also identifies under-researched motives to adopt as key ingredients in implementation configurations in which commonly discussed motives are absent. Taken together, the study concludes that understanding VSS implementation extensiveness benefits from a more holistic perspective that combines a variety of motives to adopt with implementation characteristics. Recommendations for theory and practice are included. Graphical abstract: Image 1 Highlights: Voluntary sustainability standard (VSS) implementation extensiveness is researched. VSS implementation is characterized by complex interactions between Conditions. VSS implementation extensiveness is driven by multiple implementation configurations. VSS implementation drivers include under-researched motives to adopt.